A steel-wood structure
Patent Information
- Application Number
- CN202511454114.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2025-10-13
- Publication Date
- 2026-10-09
- Estimated Expiration
- 2045-10-13
AI Technical Summary
植酸分子中的多个羟基和磷酸基团也为其提供了与其他分子相互作用的能力,形成可溶性或不溶性化合物以增加其阻燃效果,现有研究中已有植酸与壳聚糖、植酸与尿素、植酸与环糊精、植酸与硅溶胶进行复合阻燃的报道,但是目前还未见到植酸与离子液体复合用于木材阻燃的报道
本发明提供了一种钢木结构,其中木构件经过植酸和过渡金属基离子液体阻燃改性处理,植酸作为一种新型的生物质阻燃剂,具有较高的含磷量和优异的生物相容性。但单独使用植酸作为阻燃剂存在阻燃效率低、应用场景有限等问题,本发明中过渡金属基离子液体具有稳定的结构和高热稳定性,包含有阻燃基团的结构如含氮、硼、氯等,这些基团可以在火焰燃烧时发挥阻燃作用,抑制火焰的蔓延和燃烧速率,离子液体中的氢键和π-π堆积结构可以增强分子的稳定性和抗热性,有助于防止热分解和火焰传播。过渡金属在燃烧时可以催化木材基质碳化并形成更致密的保护性炭层,增加炭层的厚度,抑制热量和氧气转移到木材基质并防止热解产物进入燃烧区,这减少了热量和可燃气体的传递,从而显著减少了热量的释放。预先在过渡金属基离子液体中溶解纤维素一方面可以抑制其在浸渍时对于木材内部纤维素的溶解,另一方面纤维素通过浸渍进入木材表面和内部细胞腔、细胞间隙等易发生断裂破碎的孔隙中进行填充,增强了木材纤维骨架的韧性,从而对其力学性能起到一定的改善。
Smart Images

Figure CN121228797B_ABST
Abstract
Description
Technical Field
[0001] This invention relates to the field of composite materials, specifically a steel-wood structure. Background Technology
[0002] Steel-wood structures have a wide range of applications and are suitable for various architectural scenarios. Steel has high tensile strength and load-bearing capacity, making it suitable as the main frame; wood is lightweight and has good thermal insulation properties, making it suitable for infill or decoration. Combining the two can optimize structural performance, reduce costs and weight, and also reduce later maintenance costs.
[0003] However, the inherent flammability of wood dictates that it must undergo flame-retardant treatment when used in public places with fire protection requirements. Traditional wood flame retardants mainly include halogen-based, phosphorus-based, nitrogen-based, silicon-based, and metal oxides. These traditional flame retardants require large amounts, have poor resistance to leaching, and pose environmental pollution and potential health risks. Phytic acid, a biomass source, is widely available and abundant, possessing high phosphorus content and excellent biocompatibility. It can tightly bind to the wood matrix and impart highly efficient fire-retardant properties, and has received increasing attention in the field of wood flame retardancy in recent years. The multiple hydroxyl and phosphate groups in phytic acid molecules also provide it with the ability to interact with other molecules, forming soluble or insoluble compounds to enhance its flame-retardant effect. Existing research has reported on the composite flame retardant effects of phytic acid with chitosan, urea, cyclodextrin, and silica sol; however, there are currently no reports on the composite use of phytic acid with ionic liquids for wood flame retardancy. Summary of the Invention
[0004] Purpose of the invention: To address the above-mentioned technical problems, this invention proposes a steel-wood structure.
[0005] The technical solution adopted is as follows: A steel-wood structure, composed of steel components and wood components; The wooden components are wood that has been modified with flame retardant by phytic acid and transition metal-based ionic liquid. The anions of the transition metal-based ionic liquid contain transition metal elements.
[0006] Furthermore, the anion of the transition metal-based ionic liquid is [FeCl4]. - Or [ZnCl3] - .
[0007] Furthermore, the cationic structure of the transition metal-based ionic liquid is as follows: Where n is a positive integer ≤ 10, and R1 and R2 are each an alkyl group.
[0008] Furthermore, the preparation method of the transition metal-based ionic liquid is as follows: The intermediate is obtained by reacting N-methylimidazolium with dialkyl chloroalkylborate, and then the intermediate is reacted with a transition metal chloride.
[0009] Furthermore, the preparation method of the wooden components is as follows: The wood is first soaked in a phytic acid aqueous solution and then dried. It is then soaked a second time in a solution containing transition metal-based ionic liquid and then dried.
[0010] Furthermore, repeat the soaking, drying, second soaking, and drying steps 0-10 times.
[0011] Furthermore, the mass concentration of the phytic acid aqueous solution is 1-10%.
[0012] Furthermore, the solution containing the transition metal-based ionic liquid also contains dissolved cellulose.
[0013] Furthermore, the mass ratio of the transition metal-based ionic liquid to cellulose in the solution containing the transition metal-based ionic liquid is 5-15:1.
[0014] The beneficial effects of this invention are: This invention provides a steel-wood structure in which the wooden components are modified with phytic acid and a transition metal-based ionic liquid for flame retardancy. Phytic acid, as a novel biomass flame retardant, has a high phosphorus content and excellent biocompatibility. However, using phytic acid alone as a flame retardant has problems such as low flame retardant efficiency and limited application scenarios. In this invention, the transition metal-based ionic liquid has a stable structure and high thermal stability, containing flame-retardant groups such as nitrogen, boron, and chlorine. These groups can play a flame-retardant role during combustion, inhibiting flame spread and combustion rate. The hydrogen bonds and π-π stacking structure in the ionic liquid can enhance molecular stability and heat resistance, helping to prevent thermal decomposition and flame propagation. During combustion, the transition metal can catalyze the carbonization of the wood matrix and form a denser protective char layer, increasing the thickness of the char layer, inhibiting the transfer of heat and oxygen to the wood matrix, and preventing pyrolysis products from entering the combustion zone. This reduces the transfer of heat and combustible gases, thereby significantly reducing heat release. Pre-dissolving cellulose in a transition metal-based ionic liquid can inhibit the dissolution of cellulose inside the wood during impregnation. On the other hand, the cellulose enters the wood surface and fills the pores in the internal cell cavities and intercellular spaces that are prone to breakage, thereby enhancing the toughness of the wood fiber skeleton and improving its mechanical properties. Attached Figure Description
[0015] Figure 1 This is a flowchart illustrating the preparation route of the ionic liquid in Example 1. Detailed Implementation
[0016] Unless otherwise specified in the examples, the conditions were performed under standard conditions or as recommended by the manufacturer. Reagents or instruments whose manufacturers are not specified are all commercially available products. Techniques not mentioned in this invention refer to existing technologies. Unless otherwise specified, the following examples and comparative examples are parallel experiments, using the same processing steps and parameters.
[0017] Steel-wood structures have a wide range of applications and are suitable for various building scenarios. Steel has high tensile strength and load-bearing capacity, making it suitable as the main frame; wood is lightweight and has good thermal insulation properties, making it suitable for infill or decoration. Combining the two can optimize structural performance, reduce costs and weight, and reduce later maintenance costs. However, the inherent flammability of wood dictates that it must undergo flame-retardant treatment when used in public places with fire protection requirements.
[0018] This invention provides a steel-wood structure, which is composed of steel components and wood components; The wooden components are wood that has been modified with flame retardant by phytic acid and transition metal-based ionic liquid. The anions of the transition metal-based ionic liquid contain transition metal elements.
[0019] Phytic acid, as a novel biomass flame retardant, possesses high phosphorus content and excellent biocompatibility. However, using phytic acid alone as a flame retardant suffers from low flame retardant efficiency and limited application scenarios. Ionic liquids, on the other hand, exhibit stable structures and high thermal stability. Their anions or cations often contain flame-retardant groups, which can exert a flame-retardant effect during combustion, inhibiting flame spread and combustion rate. The hydrogen bonds and π-π stacking structures in ionic liquids enhance molecular stability and heat resistance, helping to prevent thermal decomposition and flame propagation.
[0020] This invention introduces transition metal elements into ionic liquids, which can catalyze the carbonization of the wood matrix during combustion and form a denser protective char layer. This increases the thickness of the char layer, inhibits the transfer of heat and oxygen to the wood matrix, and prevents pyrolysis products from entering the combustion zone. This reduces the transfer of heat and combustible gases, thereby significantly reducing heat release.
[0021] The anion of the transition metal-based ionic liquid is [FeCl4]. - Or [ZnCl3] - .
[0022] The current anion is [FeCl4]. - Or [ZnCl3] -Ionic liquids are mostly used for electrodeposition, nanomaterial preparation, and catalytic media, but their application in wood flame retardancy is not observed. During combustion, the dual carbonization effect of phosphorus and transition metals in phytic acid, as well as the catalytic graphitization effect of transition metals, endow the wood matrix with excellent flame retardant and smoke-suppressing properties. Chlorine is released into the gas phase as HCl during combustion, and it captures key free radicals (such as H· and HO·) in the combustion chain reaction, interrupting the combustion chain reaction and thus playing a flame-retardant role.
[0023] The cationic structure of the transition metal-based ionic liquid is as follows: Where n is a positive integer ≤ 10, and R1 and R2 are each an alkyl group.
[0024] The specific value of n can be selected from 1, 2, 3, 4, 5, 6, 7, 8, 9, 10, with 4 being the preferred value.
[0025] R1 and R2 are each an alkyl group, which can be selected from methyl, ethyl, propyl, butyl, pentyl, hexyl, heptyl, octyl, nonyl, and decyl. The methyl, ethyl, propyl, butyl, pentyl, hexyl, heptyl, octyl, nonyl, and decyl groups can be either straight-chain or branched-chain structures, and are preferably isopropyl.
[0026] The preparation method of the transition metal-based ionic liquid is as follows: The intermediate is obtained by reacting N-methylimidazolium with dialkyl chloroalkylborate, and then the intermediate is reacted with a transition metal chloride.
[0027] Specifically, equimolar amounts of N-methylimidazolium and dialkyl chloroalkylborate are placed in a flask and reacted at 80-100℃ under nitrogen protection. After the reaction is completed, the mixture is cooled to room temperature, the reaction product is washed with diethyl ether, and finally the diethyl ether is removed by rotary evaporation to obtain an intermediate. Equimolar amounts of the intermediate and ZnCl2 or FeCl3 are placed in a flask and reacted at 60-80℃ under nitrogen protection to obtain an ionic liquid.
[0028] The preparation method of the wooden components is as follows: The wood is first soaked in a phytic acid aqueous solution and then dried, and then soaked a second time in a solution containing transition metal-based ionic liquid and then dried.
[0029] The solute in the solution containing transition metal-based ionic liquids includes transition metal-based ionic liquids, and the solvent of the solution can be any organic or inorganic solvent that can be diluted and is harmless to the human body, preferably ethanol.
[0030] The process involves repeating the impregnation, drying, secondary impregnation, and drying steps 0-10 times. Too few impregnations result in limited flame-retardant modification, while too many impregnations are time-consuming and labor-intensive. The optimal number of repetitions is 5.
[0031] The phytic acid aqueous solution has a mass concentration of 1-10%.
[0032] Specifically, the mass concentration of the phytic acid aqueous solution is selected from 1%, 2%, 3%, 4%, 5%, 6%, 7%, 8%, 9%, and 10%. 5% is preferred. At this concentration, phytic acid has a relatively small weakening effect on the mechanical properties of poplar, and the flame-retardant modification effect is also relatively good.
[0033] The solution containing the transition metal-based ionic liquid also contains dissolved cellulose.
[0034] Since ionic liquids have a certain dissolving effect on cellulose in wood, pre-dissolving cellulose in transition metal-based ionic liquids can, on the one hand, inhibit the dissolution of cellulose inside the wood during impregnation, and on the other hand, allow cellulose to enter the wood surface and fill the pores in the internal cell cavities and intercellular spaces that are prone to breakage and fragmentation, thereby enhancing the toughness of the wood fiber skeleton and thus improving its mechanical properties to a certain extent.
[0035] The mass ratio of the transition metal-based ionic liquid to cellulose in the solution containing the transition metal-based ionic liquid is 5-15:1.
[0036] Specifically, the mass ratio of transition metal-based ionic liquid to cellulose can be 5:1, 6:1, 7:1, 8:1, 9:1, 10:1, 11:1, 12:1, 13:1, 14:1, or 15:1. A ratio of 10:1 is preferred.
[0037] Example 1: A steel-wood structure, consisting of steel components and wood components, which are connected and fixed by bolts; The preparation method of wooden components is as follows: 0.1 mol N-methylimidazole and 0.1 mol diisopropyl chlorobutylborate were placed in a flask and reacted at 90 °C for 48 h under nitrogen protection. After the reaction was completed, the mixture was cooled to room temperature and the reaction product was washed with 50 mL × 3 ethers. The lower layer of liquid was collected three times each time. Finally, the ether was removed by rotary evaporation to obtain an intermediate. 0.05 mol of the intermediate and 0.05 mol of ZnCl2 were placed in a flask and reacted at 70 °C for 15 h under nitrogen protection to obtain an ionic liquid. At this time, 0.1 times the mass of the ionic liquid was added to cellulose, and the mixture was kept warm and stirred until the cellulose dissolved. After cooling to room temperature, anhydrous ethanol was added to dilute the mixture to obtain an impregnation solution. Wash poplar wood measuring 100mm×100mm×10mm with clean water and dry it at 100℃ until completely dry. Dissolve phytic acid in water to obtain a 5% phytic acid aqueous solution. Soak the poplar wood in the phytic acid aqueous solution for 30 minutes, then remove it and dry it at 60℃ for 60 minutes. Soak it again in the soaking solution for 30 minutes, then remove it and dry it at 60℃ for 60 minutes. Repeat the soaking and drying steps five times, and then dry it until completely dry.
[0038] Example 2: A steel-wood structure, consisting of steel components and wood components, which are connected and fixed by bolts; The preparation method of wooden components is as follows: 0.1 mol N-methylimidazole and 0.1 mol diisopropyl chlorobutylborate were placed in a flask and reacted at 90 °C for 48 h under nitrogen protection. After the reaction was completed, the mixture was cooled to room temperature and the reaction product was washed with 50 mL × 3 ethers. The lower layer of liquid was collected three times each time. Finally, the ether was removed by rotary evaporation to obtain an intermediate. 0.05 mol of the intermediate and 0.05 mol of FeCl3 were placed in a flask and reacted at 70 °C for 15 h under nitrogen protection to obtain an ionic liquid. At this time, 0.1 times the mass of the ionic liquid was added to cellulose, and the mixture was kept warm and stirred until the cellulose dissolved. After cooling to room temperature, anhydrous ethanol was added to dilute the mixture to obtain an impregnation solution. Wash poplar wood measuring 100mm×100mm×10mm with clean water and dry it at 100℃ until completely dry. Dissolve phytic acid in water to obtain a 5% phytic acid aqueous solution. Soak the poplar wood in the phytic acid aqueous solution for 30 minutes, then remove it and dry it at 60℃ for 60 minutes. Soak it again in the soaking solution for 30 minutes, then remove it and dry it at 60℃ for 60 minutes. Repeat the soaking and drying steps five times, and then dry it until completely dry.
[0039] The difference between Example 2 and Example 1 lies in the different anions of the ionic liquid. As shown in Table 1, when the anion of the ionic liquid is [FeCl4]... - Or [ZnCl3] - The prepared wooden components all exhibit good flame-retardant properties.
[0040] Example 3: A steel-wood structure, consisting of steel components and wood components, which are connected and fixed by bolts; The preparation method of wooden components is as follows: 0.1 mol N-methylimidazole and 0.1 mol diisopropyl chlorobutylborate were placed in a flask and reacted at 90 °C for 48 h under nitrogen protection. After the reaction was completed, the mixture was cooled to room temperature and the reaction product was washed with 50 mL × 3 ethers. The lower layer of liquid was collected three times each time. Finally, the ether was removed by rotary evaporation to obtain an intermediate. 0.05 mol of the intermediate and 0.05 mol of ZnCl2 were placed in a flask and reacted at 70 °C for 15 h under nitrogen protection to obtain an ionic liquid. At this time, 0.1 times the mass of the ionic liquid was added to cellulose, and the mixture was kept warm and stirred until the cellulose dissolved. After cooling to room temperature, anhydrous ethanol was added to dilute the mixture to obtain an impregnation solution. Wash poplar wood measuring 100mm×100mm×10mm with clean water and dry it at 100℃ until completely dry. Dissolve phytic acid in water to obtain a 1% phytic acid aqueous solution. Soak the poplar wood in the phytic acid aqueous solution for 30 minutes, then remove it and dry it at 60℃ for 60 minutes. Soak it again in the soaking solution for 30 minutes, then remove it and dry it at 60℃ for 60 minutes until completely dry.
[0041] The difference between Example 3 and Example 1 is that the wood was only impregnated once and twice. Due to the small number of impregnations, the flame retardant properties of the wood components were reduced.
[0042] Example 4: A steel-wood structure, consisting of steel components and wood components, which are connected and fixed by bolts; The preparation method of wooden components is as follows: 0.1 mol N-methylimidazole and 0.1 mol diisopropyl chlorobutylborate were placed in a flask and reacted at 90 °C for 48 h under nitrogen protection. After the reaction was completed, the mixture was cooled to room temperature and the reaction product was washed with 50 mL × 3 ethers. The lower layer of liquid was collected three times each time. Finally, the ether was removed by rotary evaporation to obtain an intermediate. 0.05 mol of the intermediate and 0.05 mol of ZnCl2 were placed in a flask and reacted at 70 °C for 15 h under nitrogen protection to obtain an ionic liquid. At this time, 0.1 times the mass of the ionic liquid was added to cellulose, and the mixture was kept warm and stirred until the cellulose dissolved. After cooling to room temperature, anhydrous ethanol was added to dilute the mixture to obtain an impregnation solution. Wash poplar wood measuring 100mm×100mm×10mm with clean water and dry it at 100℃ until completely dry. Dissolve phytic acid in water to obtain a 10% phytic acid aqueous solution. Soak the poplar wood in the phytic acid aqueous solution for 30 minutes, then remove it and dry it at 60℃ for 60 minutes. Soak it again in the soaking solution for 30 minutes, then remove it and dry it at 60℃ for 60 minutes. Repeat the soaking and drying steps 10 times, and then dry it until completely dry.
[0043] The difference between Example 4 and Example 1 lies in the number of times the first and second impregnations were repeated. As shown in Table 1, the flame retardant performance of the wooden components in Example 4 after repeating the first and second impregnations 10 times was not significantly different from that in Example 1. This indicates that the number of repeated impregnations has a limited effect on improving the flame retardant performance of the wooden components.
[0044] Comparative Example 1: It is basically the same as Example 1, except that 1-butyl-3-methylimidazole chloride is used instead of the self-made ionic liquid.
[0045] A steel-wood structure, consisting of steel components and wood components, which are connected and fixed by bolts; The preparation method of wooden components is as follows: Add 0.1 times the mass of cellulose to 1-butyl-3-methylimidazole chloride, keep warm and stir at 70°C until the cellulose dissolves, cool to room temperature, and then add 10 times the mass of anhydrous ethanol to dilute it to obtain the impregnation solution. Wash poplar wood measuring 100mm×100mm×10mm with clean water and dry it at 100℃ until completely dry. Dissolve phytic acid in water to obtain a 5% phytic acid aqueous solution. Soak the poplar wood in the phytic acid aqueous solution for 30 minutes, then remove it and dry it at 60℃ for 60 minutes. Soak it again in the soaking solution for 30 minutes, then remove it and dry it at 60℃ for 60 minutes. Repeat the soaking and drying steps five times, and then dry it until completely dry.
[0046] As can be seen from the comparison between Example 1 and Comparative Example 1 in Table 1, the transition metal-based ionic liquid in Example 1 provides a greater improvement in the flame retardant properties of wood components compared to 1-butyl-3-methylimidazole chloride.
[0047] Comparative Example 2: It is basically the same as Example 1, except that 1-butyl-3-methylimidazole chloride is used instead of the intermediate.
[0048] A steel-wood structure, consisting of steel components and wood components, which are connected and fixed by bolts; The preparation method of wooden components is as follows: Take 0.05 mol of 1-butyl-3-methylimidazolium chloride and 0.05 mol of ZnCl2 in a flask, and react at 70℃ for 15 h under nitrogen protection to obtain an ionic liquid. Then add 0.1 times the mass of cellulose of the ionic liquid, continue to keep warm and stir until the cellulose dissolves, cool to room temperature, and then add 10 times the mass of anhydrous ethanol of the ionic liquid to dilute it to obtain the impregnation solution. Wash poplar wood measuring 100mm×100mm×10mm with clean water and dry it at 100℃ until completely dry. Dissolve phytic acid in water to obtain a 5% phytic acid aqueous solution. Soak the poplar wood in the phytic acid aqueous solution for 30 minutes, then remove it and dry it at 60℃ for 60 minutes. Soak it again in the soaking solution for 30 minutes, then remove it and dry it at 60℃ for 60 minutes. Repeat the soaking and drying steps five times, and then dry it until completely dry.
[0049] As can be seen from the comparison between Example 1 and Comparative Example 2 in Table 1, the cationic structure in Example 1 provides a greater improvement in the flame retardant properties of wood components compared to 1-butyl-3-methylimidazole chloride.
[0050] Comparative Example 3: It is basically the same as Example 1, except that chitosan solution is used as the impregnation liquid.
[0051] Dissolve 1g of chitosan in 99g of acetic acid (2% by mass) solution and stir well to obtain an impregnation solution. Wash poplar wood with dimensions of 100mm×100mm×10mm with clean water and dry it at 100℃ until completely dry. Dissolve phytic acid in water to obtain a 5% phytic acid aqueous solution. Immerse the poplar wood in the phytic acid aqueous solution for 30 minutes, then remove it and dry it at 60℃ for 60 minutes. Immerse it again in the impregnation solution for 30 minutes, then remove it and dry it at 60℃ for 60 minutes. Repeat the first immersion and drying and the second immersion and drying steps 5 times, and then dry it until completely dry.
[0052] As can be seen from the comparison between Example 1 and Comparative Example 3 in Table 1, the impregnation solution containing transition metal-based ionic liquid in Example 1 has a greater improvement in the flame retardant performance of wood components compared to chitosan solution.
[0053] Comparative Example 4: It is basically the same as Example 1, except that cellulose is not added.
[0054] A steel-wood structure, consisting of steel components and wood components, which are connected and fixed by bolts; The preparation method of wooden components is as follows: 0.1 mol N-methylimidazole and 0.1 mol diisopropyl chlorobutylborate were placed in a flask and reacted at 90 °C for 48 h under nitrogen protection. After the reaction was completed, the mixture was cooled to room temperature and the reaction product was washed with 50 mL × 3 ethers. The lower layer of liquid was collected three times each time. Finally, the ether was removed by rotary evaporation to obtain an intermediate. 0.05 mol of the intermediate and 0.05 mol of ZnCl2 were placed in a flask and reacted at 70 °C for 15 h under nitrogen protection to obtain an ionic liquid. The ionic liquid was diluted with 10 times its mass of anhydrous ethanol to obtain an impregnation solution. Wash poplar wood measuring 100mm×100mm×10mm with clean water and dry it at 100℃ until completely dry. Dissolve phytic acid in water to obtain a 5% phytic acid aqueous solution. Soak the poplar wood in the phytic acid aqueous solution for 30 minutes, then remove it and dry it at 60℃ for 60 minutes. Soak it again in the soaking solution for 30 minutes, then remove it and dry it at 60℃ for 60 minutes. Repeat the soaking and drying steps five times, and then dry it until completely dry.
[0055] As can be seen from the comparison between Example 1 and Comparative Example 4 in Table 1, the addition of cellulose to the impregnation solution can improve the mechanical strength of wooden components to a certain extent.
[0056] Comparative Example 5: The process is basically the same as in Example 1, except that phytic acid aqueous solution is used alone to modify poplar wood for flame retardancy.
[0057] A steel-wood structure, consisting of steel components and wood components, which are connected and fixed by bolts; The preparation method of wooden components is as follows: Wash poplar wood measuring 100mm×100mm×10mm with clean water and dry it at 100℃ until completely dry. Dissolve phytic acid in water to obtain a 5% phytic acid aqueous solution. Soak the poplar wood in the phytic acid aqueous solution for 30 minutes, then remove it and dry it at 60℃ for 60 minutes. Repeat the soaking-drying process 5 times and then dry it until completely dry.
[0058] As can be seen from the comparison between Example 1 and Comparative Example 5 in Table 1, the flame retardant performance of wood components can be significantly improved by using phytic acid aqueous solution and impregnation solution containing transition metal-based ionic liquid for joint flame retardant treatment.
[0059] Performance testing: The wooden components prepared in Examples 1-4 and Comparative Examples 1-5 of this invention, as well as the completely dried poplar wood (blank group), were used as samples for performance testing.
[0060] According to ISO-5660-1:2015 "Tests for reaction to fire - Heat release, smoke production and rate of mass loss - Part 1: Heat release rate (cone calorimeter method)", the ignition time and total heat release of the sample were tested, and the thermal radiation power was 50 kW·m. -2 Each group was tested 5 times, and the average value was taken as the final test result.
[0061] The mechanical properties of the specimens were tested using an electronic universal testing machine. Bending strength was determined according to standard ASTM D790-03, with a test span of 80 mm and a test speed of 5 mm / min. Each test was performed five times, and the average value was taken as the final result.
[0062] The test results are shown in Table 1 below.
[0063] As shown in Table 1 above, the wooden components prepared by the present invention have good flame retardant properties, with the advantages of long ignition time, low total heat release, and only a slight decrease in mechanical properties.
[0064] The above embodiments are only used to illustrate the technical solutions of the present invention, and are not intended to limit it. Although the present invention has been described in detail with reference to the foregoing embodiments, those skilled in the art should understand that modifications can still be made to the technical solutions described in the foregoing embodiments, or equivalent substitutions can be made to some of the technical features. Such modifications or substitutions do not cause the essence of the corresponding technical solutions to deviate from the spirit and scope of the technical solutions of the embodiments of the present invention.
Claims
1. A steel-wood structure, characterized in that, Composed of steel and wood components; The wooden components are wood that has been modified with flame retardant by phytic acid and transition metal-based ionic liquid. The anion of the transition metal-based ionic liquid is [FeCl4]. - Or [ZnCl3] - ; The cationic structure of the transition metal-based ionic liquid is as follows: ; Where n is 4, and R1 and R2 are isopropyl; The preparation method of the transition metal-based ionic liquid is as follows: The intermediate is obtained by reacting N-methylimidazolium with diisopropyl chlorobutylborate, and then the intermediate is reacted with a transition metal chloride. The preparation method of wooden components is as follows: The wood is first soaked in phytic acid aqueous solution and then dried, and then soaked a second time in solution containing transition metal ion liquid and then dried. The solution containing the transition metal-based ionic liquid also contains dissolved cellulose; The mass ratio of the transition metal-based ionic liquid to cellulose in the solution containing the transition metal-based ionic liquid is 5-15:
1.
2. The steel-wood structure as described in claim 1, characterized in that, Repeat the soaking, drying, second soaking, and drying steps 0-10 times.
Citation Information
Patent Citations
Wooden-structure building beam-column joint structure
CN105178448A
Phytic acid flame-retardant wood and preparation method thereof
CN110524657A
Metal-based ionic liquid compound flame retardant and method for preparing flame-retardant wood by using same
CN120206599A